European welfare state under the policy "make work pay" : Analysis with composite indicators - Andranik S. Tangian (Hans-Böckler-Stiftung, Wirtschafts- und Sozialwissenschaftliches Institut (WSI), 2005)
The social security systems in 22 European countries are evaluated with a specially constructed indicator. It is based on a census-simulating model which combines both empirical (statistical) and normative (rule-based) approaches. The individual answers of unemployed on social security benefits are normatively derived from their personal situations with the OECD Tax-Benefit Models. The empirical data about personal situations are available from EuroStat. The goal is estimating the national average of net replacement rates (NRR) for unemployed persons. Such an indicator of social security shows the average degree with which social benefits compensate the loss of previous earnings. Thus, the paper suggests: * (Methodology) a model of census simulation combining statistical data on the population with individual answers computed with a rule-based model, * (Indicator) an integral quantitative evaluation of social security in Europe, which reveals its total decline by 2004 contrary to institutional improvements, * (Analysis) an explanation of the decline by a structural change of European labour markets with rapidly growing 'atypical' employment groups (= part-time, temporary, self-employed, etc.) with a lower eligibility to social benefits than normally employed (= permanently full-time), * (Policy implications) a possible resolution of European policy contradictions by the "basic income model" with "flexinsurance".
Keywords: C51; J32; C43; J38; 330; Composite indicators; social security; European welfare state; European Union; "make work pay" policy